Viral Effect or Personal Impression? Role of Content Marketing, Customer Experience on Repurchase Intention - Riwu, Yonas Ferdinand; Natonis, Sari Angriany; Nastiti, Dyah Wahyu (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to determine the influence of Content Marketing and Customer Experience on Repurchase Interest in Ventela Brands by using quantitative research methods. The data collection technique used questionnaires that were distributed to management students of Nusa Cendana University. The samples in this study were taken using Purposive Sampling. This study was conducted on Ventela Brand users with a sample of 100 people. The data was analyzed with the help of SPSS software with multiple linear regression methods. The results of this study clearly show that content marketing and customer experience have a significant influence on repurchase interest. These results provide a clear direction: personal impressions through customer experience and content quality are more dominant in influencing repurchase intent than content virality. In other words, personal impression has been proven to be a determining factor in consumers' decision to buy again, not solely exposure to viral content. Content marketing strategies that are informative, educational, and consistent create added value that strengthens consumers' emotional connection to the brand. Consumers are not only exposed to content, but feel personally connected because it provides real benefits. These findings reinforce the approach of value-based content, rather than click-based content, in building loyalty. Meanwhile, customer experience has proven to play a central role in creating a deep impression. Positive experiences in both service interaction, product quality, and digital atmosphere lead to strong emotional engagement, which is the foundation for repurchase intent.